International migration and regional integration: dialogue between Mercosur and Unasur - Coutinho, Beatriz Isola (2014)
This article introduces a discussion about Mercosur and Unasur while macro- -structural participants in South-America contemporary immigration. Given by the relation between immigrant phenomenon and the regional integration process, we search to insert preliminary considerations about the theme focusing the main aspects raised in politician speech, considering them basic spaces for reflections and proposals about actually displacements.